Involvement of the endogenous opioid system in the psychopharmacological actions of ethanol: the role of acetaldehyde - Font, Laura; Luján, Miguel Ángel; Pastor, Raúl (Frontiers in Behavioral Neuroscience, 2013)
Significant evidence implicates the endogenous opioid system (opioid peptides and receptors) in the mechanisms underlying the psychopharmacological effects of ethanol. Ethanol modulates opioidergic signaling and function at different levels, including biosynthesis, release, and degradation of opioid peptides, as well as binding of endogenous ligands to opioid receptors. The role of β-endorphin and µ-opioid receptors (OR) have been suggested to be of particular importance in mediating some of the behavioral effects of ethanol, including psychomotor stimulation and sensitization, consumption and conditioned place preference. Ethanol increases the release of β-endorphin from the hypothalamic arcuate nucleus (NArc), which can modulate activity of other neurotransmitter systems such as mesolimbic dopamine. The precise mechanism by which ethanol induces a release of β-endorphin, thereby inducing behavioral responses, remains to be elucidated. The present review summarizes accumulative data suggesting that the first metabolite of ethanol, the psychoactive compound acetaldehyde, could participate in such mechanism. Two lines of research involving acetaldehyde are reviewed: 1) implications of the formation of acetaldehyde in brain areas such as the NArc, with high expression of ethanol metabolizing enzymes and presence of cell bodies of endorphinic neurons and 2) the formation of condensation products between DA and acetaldehyde such as salsolinol, which exerts its actions via OR.